Negative electrode for lithium metal battery, method for manufacturing the same, and lithium metal battery containing the same
By forming a protective layer of a high-content lithium storage material on the negative electrode of the lithium metal battery, the reactivity problem of the lithium metal battery during assembly is solved, the battery life is extended and the energy density is improved.
Patent Information
- Application Number
- CN202180006015.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-02
- Filing Date
- 2021-11-01
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-11-01
AI Technical Summary
The negative electrode of the lithium metal battery reacts with the atmosphere during assembly, resulting in an increase in the thickness of the lithium battery deposition layer and frequent side reactions of the electrolyte, which shortens the battery life.
A protective layer is formed on the negative electrode of the lithium metal battery, which contains a material capable of sucking and releasing lithium at more than 70% of the weight, such as a carbon-based material, a lithium metal oxide or an alloy thereof, combined with a metal current collector base The material and the conductive material form a protective layer with a thickness of 1 μm to 100 μm to reduce the thickness and resistance of the lithium electrode deposited layer.
By reducing the thickness and resistance of the lithium battery deposition layer, the energy density and life characteristics of the battery are improved, and the side reactions of the electrolyte are reduced.
Smart Images

Figure BDA0003607486320000201
Abstract
Description
Technical Field
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0144665 filed in the Korean Intellectual Property Office on November 2, 2020, the disclosure of which is incorporated herein by reference in its entirety.
[0003] The present disclosure relates to a negative electrode for a lithium metal battery, a method for manufacturing the same, and a lithium metal battery including the same. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative energy or clean energy, and as part of this, the field that is being most actively researched is the field of power generation and storage using electrochemistry.
[0005] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to gradually expand.
[0006] In recent years, with the increase in technical development and demand for mobile devices such as portable computers, portable phones and cameras, the demand for secondary batteries as energy sources has also increased dramatically. Among such secondary batteries, lithium secondary batteries exhibit high charge / discharge characteristics and life characteristics and are environmentally friendly, and many studies have been conducted on them and they are now commercialized and widely used.
[0007] Generally, a secondary battery has a structure in which a non-aqueous electrolyte is impregnated into an electrode assembly including a positive electrode, a negative electrode and a porous separator. In addition, the positive electrode is generally manufactured by coating a positive electrode mixture containing a positive electrode active material on an aluminum foil, and the negative electrode is manufactured by coating a negative electrode mixture containing a negative electrode active material on a copper foil.
[0008] Generally, a lithium transition metal oxide is used as a positive electrode active material, and a carbon-based material is used as a negative electrode active material.
[0009] However, recently, lithium metal batteries using lithium metal itself exhibiting high energy density as a negative electrode active material have been commercialized.
[0010] At this time, since lithium metal used as the negative electrode has a low density (0.54 g / cm 3) and a very low standard reduction potential (-3.045V SHE: standard hydrogen electrode), so it is a material that has attracted great attention as a negative electrode material for high energy density batteries. In addition, despite the problems caused by the very high chemical activity, recently, with the steady increase in the use of mobile communications and portable electronic devices and their rapid development, the demand for the development of secondary batteries with high energy density continues to increase. Therefore, the necessity of using lithium metal negative electrodes continues to emerge.
[0011] In this case, when a lithium metal electrode is used as a negative electrode, lithium metal has very excellent reactivity, so during the assembly of the secondary battery, the lithium metal reacts with the atmosphere and disintegrates, and the lithium electrodeposition layer formed by charging causes serious side reactions by direct contact with the electrolyte, which leads to rapid deterioration of life characteristics.
[0012] Therefore, there is a need to develop a negative electrode that can solve the above problems and thus can be used in lithium metal batteries. Summary of the invention
[0013]
Technical issues
[0014] The present disclosure is designed to solve the above-mentioned problems and other technical problems that have yet to be resolved.
[0015] Specifically, an object of the present disclosure is to provide a negative electrode capable of reducing resistance by minimizing the reaction of the negative electrode with the atmosphere during assembly of a secondary battery.
[0016] Another object of the present disclosure is to minimize the thickness of a lithium electrodeposition layer formed during operation of a lithium metal battery using the negative electrode, increase the electrodeposition density, and prevent side reactions of the electrolyte, thereby improving life characteristics.
[0017]
Technical solution
[0018] In order to achieve the above object, according to one embodiment of the present disclosure, there is provided a negative electrode for a lithium metal battery, comprising: a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, and a protective layer formed on the lithium metal layer,
[0019] The protective layer contains a material capable of occluding and releasing lithium in an amount of 70 wt % or more based on the total weight.
[0020] Here, the material capable of absorbing and releasing lithium includes carbon-based materials, lithium metal oxides, metal compounds capable of alloying with lithium, metal oxides, lithium-metal alloys or a mixture of two or more thereof, and specifically, may be carbon-based materials, SnO2 or a mixture thereof.
[0021] The metal current collector substrate may be one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper surface-treated with a different metal, stainless steel surface-treated with a different metal, and aluminum-cadmium alloy.
[0022] The metal current collector substrate may be a metal including copper.
[0023] In a specific embodiment, the lithium metal layer may have a thickness of 1 μm to 70 μm.
[0024] In a specific embodiment, the material capable of absorbing and releasing lithium in the protective layer is specifically a carbon-based material, lithium titanium oxide as a lithium metal oxide, a Si-based material or a Sn-based material as a metal compound or a metal oxide, or a mixture thereof.
[0025] In a specific embodiment, the protective layer may have a porosity of 1% to 70%, and a thickness thereof may be in a range of 1 μm to 100 μm.
[0026] The protective layer may further include an adhesive and a conductive material.
[0027] According to another embodiment of the present disclosure, a method for manufacturing the negative electrode is provided, the method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) mixing particles of a material capable of absorbing and releasing lithium with a solvent to prepare a slurry; and (c) coating the slurry onto the lithium metal of step (a), wherein the particles of step (b) have a particle size of 1 μm to 30 μm.
[0028] Here, the material capable of absorbing and releasing lithium may include a carbon-based material, SnO 2 or a mixture thereof.
[0029] At this time, in the step (b), the slurry may be prepared such that the solid content of the slurry accounts for 30 volume % to 80 volume % based on the total volume of the slurry.
[0030] According to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode according to item 1, the method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) dispersing particles of a material capable of absorbing and releasing lithium in a solvent to prepare a dispersion; and (c) coating the dispersion onto the lithium metal of step (a), wherein the particles of step (b) have a particle size of 1 nm to 1000 nm.
[0031] The material capable of absorbing and releasing lithium may include a carbon-based material, SnO 2 or a mixture thereof.
[0032] Here, in the step (b), the slurry may be prepared such that the solid content of the dispersion accounts for 0.1 volume % to 30 volume % based on the total volume of the dispersion.
[0033] According to another embodiment of the present disclosure, a lithium metal battery is provided, wherein an electrode assembly is constructed in a battery shell together with a lithium non-aqueous electrolyte, and the electrode assembly comprises: a negative electrode according to item 1; a positive electrode having a structure in which a positive electrode mixture comprising active materials is coated on at least one surface of a positive electrode collector; and a separator interposed between the negative electrode and the positive electrode.
[0034] At this time, the negative electrode further includes a lithium electrodeposition layer formed by precipitating lithium on the protective layer, and the lithium electrodeposition layer may have a lithium density of 0.13 g / cc to 0.54 g / cc. DETAILED DESCRIPTION
[0035] Hereinafter, for a better understanding of the present disclosure, the present disclosure will be described in more detail.
[0036] The terms and words used in this specification and claims should not be construed as limited to general terms or terms in a dictionary, and the present disclosure should be interpreted with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventors can appropriately define the concepts of the terms in order to appropriately describe their own disclosure in the best manner.
[0037] The technical terms provided herein are only used for the purpose of describing specific embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include the plural forms as well.
[0038] In addition, throughout the specification, unless otherwise stated, when a part is referred to as “comprising” a certain component, it means that the part may further include other components, rather than excluding the other components.
[0039] According to one embodiment of the present disclosure, a negative electrode for a lithium metal battery is provided, comprising: a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, and a protective layer formed on the lithium metal layer, wherein the protective layer comprises a material capable of absorbing and releasing lithium in an amount of more than 70 wt % based on the total weight.
[0040] The metal current collector substrate may be one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper surface-treated with a different metal, stainless steel surface-treated with a different metal, and aluminum-cadmium alloy.
[0041] The metal current collector substrate may be a metal including copper.
[0042] The lithium metal layer is a negative electrode active material, and its thickness and amount may be determined according to the desired purpose, but is not limited thereto. For example, the lithium metal layer may have a thickness of 1 μm to 70 μm, more particularly 5 μm to 70 μm, and more specifically 10 μm to 50 μm.
[0043] When the thickness is too thin and exceeds the above range, lithium as an active material is insufficient, and thereafter, a lithium electrodeposition layer is formed during charging and discharging of the secondary battery and functions as an active material. Therefore, when the thickness is too thick, the energy density relative to the volume may be reduced, so it is most preferable to satisfy the above range.
[0044] On the other hand, the protective layer may contain a material capable of occluding and releasing lithium, and specifically, may be composed of the materials described below.
[0045] That is, in order to achieve the effect of the present disclosure, the protective layer must substantially contain a material capable of absorbing and releasing lithium. If the material is not a material capable of absorbing and releasing lithium, the lithium metal layer can be protected from being affected by the atmosphere during the assembly process of the secondary battery, but in the subsequent charging and discharging process of the secondary battery, the protective layer cannot absorb and release lithium, and therefore, when a lithium electrodeposition layer is formed on the protective layer by charging and discharging, the protective layer does not absorb lithium, and therefore, lithium cannot actually be directly electrodeposited, and thus it becomes impossible to reduce the thickness of the lithium electrodeposition layer. Therefore, since the lithium electrodeposition layer is formed thickly at a low density as in the conventional case, it is difficult to prevent the side reaction of the electrolyte, and instead the ratio of energy density to volume is reduced due to the protective layer, which is not preferred.
[0046] Therefore, the material capable of absorbing and releasing lithium is preferably a material capable of being used as an active material of a conventional negative electrode, and it may be, for example, a carbon-based material, a lithium metal oxide, a metal compound capable of alloying with lithium, a metal oxide, a lithium-metal alloy, or a mixture of two or more thereof. Specifically, it may be a carbon-based material as a high-capacity material capable of absorbing lithium, a lithium-titanium oxide as a lithium metal oxide, a Si-based material or a Sn-based material as a metal compound or a metal oxide, or a mixture thereof. More specifically, a carbon-based material, SnO2, or a mixture thereof is most preferred.
[0047] The carbon-based material may be, for example, carbon such as artificial graphite, natural graphite, graphitized carbon fiber, graphene, or amorphous carbon.
[0048] The lithium metal oxide may be, for example, Li x Fe2O3(0≤x≤1), Lix WO2(0≤x≤1), Li a Ti b O4(0.5≤a≤3, 1≤b≤2.5), Li4Ti5O 12 wait.
[0049] The metal compound capable of being alloyed with lithium may be a compound containing a metal that forms an alloy with lithium, which may be a metal such as nickel, Al, Ge, Mg, Zn, Ag, Si, or Sn.
[0050] In addition, the metal oxide may be, for example, titanium dioxide, SiO x (1≤x≤2), SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 or Bi2O5.
[0051] Finally, the metal in the lithium-metal alloy can be a metal such as Na, K, Rb, Cs, Fr, Be, Sr, Ba, Ra, Mg, Ca, Al, Ge, Pb, As, Sb, Bi, Ag, Zn, Cd, P or Hg, and the lithium-metal alloy can be an alloy of the above metals and lithium.
[0052] On the other hand, the protective layer may contain a material generally used as a negative electrode active material. In the absence of a binder, the binder effect may be supplemented by coating, drying and rolling, and a conductive material may not be contained. However, when the thickness of the protective layer becomes thicker, a binder for further bonding them and a conductive material for enhancing conductivity may be additionally contained.
[0053] Specific examples of the binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof. The ratio of the material capable of absorbing and releasing lithium to the binder may be 7:3 to 99:1 based on their weight.
[0054] When the content of the binder is too large and exceeds the above range, it is difficult to fully demonstrate the effect of improving the electrodeposition density of the lithium electrodeposition layer attempted to be achieved by forming the protective layer. When the content of the binder is too small, it cannot be well bonded to the lithium metal layer, which is not preferred.
[0055] On the other hand, such a protective layer is different from the active material layer formed on the negative electrode in a general battery.
[0056] Specifically, they can actually react with lithium and accept lithium by charging, but a lithium electrodeposition layer is formed on these protective layers in a larger amount than the active material layer, and such a lithium electrodeposition layer is used as an active material together with the lithium metal layer.
[0057] Therefore, it is preferred that the lithium metal layer present at the lower part of the protective layer and the lithium electrodeposition layer present at the upper part of the protective layer are connected in the form of the absorbed lithium. For this purpose, the protective layer having a porosity above a predetermined range enables the lithium metal layer to be connected to the lithium electrodeposition layer by inserting lithium into the protective layer.
[0058] Therefore, the protective layer preferably has a porosity of 1% or more, specifically 10% or more, more specifically 20% or more. In order to make the protective layer have a predetermined strength and reduce the thickness of the lithium electrodeposition layer by the lithium absorption mechanism, a material capable of absorbing and releasing at least a certain portion of lithium is required, and therefore preferably has a porosity of 70% or less, specifically 60% or less, more specifically 50% or less. Such porosity can vary depending on the solid content, drying conditions, preparation method, etc. Specifically, when prepared using the following slurry, the porosity can be formed in the range of 20% to 70%, and when prepared using a dispersant, the porosity can be formed in the range of 1% to 30%.
[0059] In addition, the protective layer is formed in a relatively thin range as an additional structure, and it is expected that the energy density of the lithium metal battery relative to the volume is not reduced. Specifically, the protective layer can have a thickness of 0.1 μm to 100 μm, more specifically 1 μm to 60 μm, and most specifically 1 μm to 50 μm.
[0060] When the protective layer is formed too thick and exceeds the above range, a large amount of lithium is embedded in such a protective layer, so that the lithium electrodeposition layer cannot be sufficiently obtained by electrodeposition, and high energy density cannot be obtained. When the protective layer is formed too thin, the effect of improving the electrodeposition density of lithium by charging / discharging as expected by the present disclosure cannot be obtained, which is not preferred.
[0061] According to another embodiment of the present invention, a method for manufacturing the negative electrode is provided, the method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) mixing particles of a material capable of absorbing and releasing lithium with a solvent to prepare a slurry; and (c) coating the slurry onto the lithium metal of step (a), wherein the particles of step (b) have a particle size of 1 μm to 30 μm.
[0062] Alternatively, according to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode according to item 1, the method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) dispersing particles of a material capable of absorbing and releasing lithium in a solvent to prepare a dispersion; and (c) coating the dispersion onto the lithium metal of step (a), wherein the particles of step (b) have a particle size of 1 nm to 1000 nm.
[0063] That is, the manufacturing method forms a protective layer by coating on the lithium metal layer formed on at least one surface of the metal current collector substrate, but the manufacturing method differs depending on the particle size of the particles of the material capable of absorbing and releasing lithium contained in the protective layer.
[0064] Specifically, when the particle size is relatively large, the step can be performed by preparing a slurry such as an active material slurry and applying it to the lithium metal layer. When the particle size is small, the step can be performed by preparing a pre-dispersion containing these particles and applying it to the lithium metal layer, as in the method of preparing a conductive material pre-dispersion.
[0065] The particle size is the average diameter of the particles (D50), which means the particle size corresponding to the 50% point in the cumulative distribution of the number of particles relative to the particle size. In other words, D50 is the particle size corresponding to the 50% point in the cumulative distribution of the number of particles relative to the particle size.
[0066] D50 can be measured by using a laser diffraction method. Specifically, the powder to be tested is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500). When the particles pass through the laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. D50 can be measured by calculating the particle size corresponding to 50% of the points in the cumulative distribution of the number of particles relative to the particle size in the analyzer.
[0067] Specifically, the particle size of the particles having a larger particle size may be particularly 3 μm to 20 μm, more particularly 5 μm to 15 μm.
[0068] In the preparation method as described above, in order to satisfy the effect according to the present disclosure, it is more preferred to adjust the porosity, thereby preparing the slurry so that the content of the solid contained in the slurry accounts for 30 volume % to 80 volume % based on the total volume of the slurry, or preparing the dispersion so that the solid content of the dispersion accounts for 0.1 volume % to 30 volume % based on the total volume of the dispersion. The prepared slurry or dispersion may be applied and dried to adjust the porosity.
[0069] The material capable of absorbing and releasing lithium may be a carbon-based material, lithium titanium oxide as a lithium metal oxide, a Si-based material or a Sn-based material as a metal compound or a metal oxide, or a mixture thereof, more specifically, a carbon-based material, SnO2 or a mixture thereof.
[0070] According to another embodiment of the present disclosure, a lithium metal battery is provided, wherein an electrode assembly is constructed in a battery case together with a lithium non-aqueous electrolyte, the electrode assembly comprising: the negative electrode; a positive electrode having a structure in which a positive electrode mixture comprising active materials is coated on at least one surface of a positive electrode collector; and a separator interposed between the negative electrode and the positive electrode.
[0071] The positive electrode has a structure in which a positive electrode mix including an active material is coated on at least one surface of a positive electrode current collector.
[0072] The positive electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector may have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to increase the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0073] The positive electrode active material as an active material may include, for example, a layered compound such as lithium nickel oxide (LiNiO2), or a compound substituted by one or more transition metals; lithium manganese oxide, such as a chemical formula Li 1+x Mn 2-x O4 (where x = 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, with the chemical formula LiNi 1-x M x O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-x M x O2 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiMn2O4, wherein a portion of Li in the chemical formula is replaced by alkaline earth metal ions; disulfide compounds; Fe2(MoO4)3, etc., but are not limited thereto.
[0074] The positive electrode mixture may further include a conductive material and a binder in addition to the positive electrode active material.
[0075] The conductive material is generally added in an amount of 0.1 wt % to 30 wt %, specifically 1 wt % to 10 wt %, more specifically 1 wt % to 5 wt %, based on the total weight of the positive electrode mixture layer. The conductive material is not particularly limited as long as it has high conductivity without causing chemical changes in the corresponding battery, for example, graphite such as natural graphite or artificial graphite; carbon blacks such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives.
[0076] The binder is a component that assists the combination of active materials, conductive materials, etc. and the combination with the current collector, and is based on the total weight of the positive electrode active material layer, and can be added in an amount of 0.1% to 30% by weight, specifically 1% to 10% by weight. Examples of the binder may include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.
[0077] The separator is an insulating film with high ion permeability and mechanical strength. The pore size of the separator is generally 0.01 μm to 10 μm, and the thickness is generally 5 μm to 300 μm. As such a separator, for example, a chemically resistant and hydrophobic olefin polymer such as polypropylene; a sheet or nonwoven fabric made of glass fiber or polyethylene is used. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also serve as a separator.
[0078] The lithium non-aqueous electrolyte generally includes a lithium salt and a non-aqueous solvent. As the non-aqueous solvent, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc. are used, but are not limited thereto.
[0079] As examples of the nonaqueous electrolyte, there can be mentioned aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate.
[0080] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, and the like.
[0081] Examples of the inorganic solid electrolyte include nitrides, halides and sulfates of lithium (Li), such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0082] The lithium salt is a material that is easily dissolved in the non-aqueous electrolyte. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate and lithium imide.
[0083] In addition, in order to improve the charge / discharge characteristics, flame retardancy, etc., the nonaqueous electrolyte may further contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, in order to impart non-flammability, the electrolyte may also include a halogen-containing solvent such as carbon tetrachloride and trifluoroethylene. In addition, in order to improve high temperature storage characteristics, the electrolyte may also include carbon dioxide gas. In addition, the electrolyte may also include fluoroethylene carbonate (FEC), propylene sultone (PRS), etc.
[0084] The battery case is not limited as long as it has a structure capable of accommodating the electrode assembly, and may be a pouch type battery, or a prismatic or cylindrical battery case made of a metal can, which is known in the art.
[0085] On the other hand, the lithium metal battery is manufactured by introducing an electrode assembly together with a lithium nonaqueous electrolyte into a battery case, sealing the case, and activating the battery, wherein the negative electrode may further include a lithium electrodeposition layer formed due to lithium precipitation on the protective layer.
[0086] Specifically, when lithium is charged into the protective layer, lithium is first intercalated into the protective layer, and then lithium electrodeposition is performed on the protective layer.
[0087] Therefore, according to the present disclosure, since the lithium electrodeposition layer must be included in essence, the amount of lithium provided by the positive electrode must exceed the amount that can be embedded in the protective layer of the negative electrode, for example. In other words, if the amount of lithium that the positive electrode can provide is referred to as the positive electrode loading (e.g., 5 mAh / cm 2 ), and the lithium insertion capacity of the protective layer formed on the negative electrode is referred to as the negative electrode loading capacity (e.g. 1 mAh / cm 2 ), then up to 1mAh / cm 2 Li forms Li9Al4, and 4 mAh / cm 2 A lithium electrodeposition layer is formed.
[0088] The lithium electrodeposition layer is also used as a negative electrode active material. In the past, when no protective layer was formed, the electrodeposition density of the lithium electrodeposition layer was 0.1 g / cc or less, which means that the electrodeposition density was low and thick, the reaction area with the electrolyte was wide, and the life characteristics deteriorated rapidly. However, according to the present disclosure, while the protective layer plays the role of absorbing a predetermined portion of lithium, the electrodeposition density of the lithium electrodeposition layer is increased from 0.13 g / cc to 0.54 g / cc, and the thickness is reduced, so the side reaction with the electrolyte is reduced, thereby showing improved life characteristics.
[0089] Hereinafter, the preferred embodiments of the present disclosure, the comparative examples for comparison with them, and the experimental examples for evaluating them are described. However, it will be apparent to those skilled in the art that these embodiments are only for illustrative purposes, and various changes and modifications may be made without departing from the scope and spirit of the present invention, and such changes and modifications certainly fall within the scope of the appended claims.
[0090] <Comparative Example 1>
[0091] A commercially available copper current collector (I2B, Iljin Materials Co., Ltd.) was prepared as a metal current collector substrate.
[0092] A lithium foil (Li foil, thickness: 60 μm) was placed opposite to one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they did not separate, forming a lithium metal layer. Thus, a negative electrode was obtained.
[0093] <Comparative Example 2>
[0094] A commercially available copper current collector (I2B, Iljin Materials Co., Ltd.) was prepared as a metal current collector substrate.
[0095] A lithium foil (Li foil, thickness: 25 μm) was placed opposite to one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they did not separate, forming a lithium metal layer. Thus, a negative electrode was obtained.
[0096] <Example 1>
[0097] A commercially available copper current collector (I2B, Iljin Materials Co., Ltd.) was prepared as a metal current collector substrate.
[0098] A lithium foil (Li foil, thickness: 20 μm) was placed opposite to one surface of a copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they did not separate, forming a lithium metal layer.
[0099] In addition, artificial graphite (particle size (D50): 9 μm) and a binder (PVDF) were mixed in an NMP solvent at a weight ratio of 9:1 so that the volume ratio of the solid component:NMP solvent was 5:5, thereby forming a protective layer slurry. The obtained slurry was applied on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm. Thus, a negative electrode was obtained.
[0100] <Example 2>
[0101] A negative electrode was obtained in the same manner as in Example 1, except that artificial graphite (particle size (D50): 25 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0102] <Example 3>
[0103] The negative electrode was obtained in the same manner as in Example 1, except that the lithium metal oxide Li4Ti5O 12 (particle size (D50): 3 μm) and a binder (PVDF) are mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent is 5:5, thereby forming a protective layer slurry, and the resulting slurry is coated on a lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0104] <Example 4>
[0105] A negative electrode was obtained in the same manner as in Example 1, except that graphene spheres (particle size (D50): 200 nm) and a binder (PVDF) were dispersed in an NMP solvent in a weight ratio of 7:3 so that the volume ratio of the solid component:NMP solvent was 1:9, thereby forming a dispersion, and the resulting dispersion was coated on a lithium metal layer and dried to form a protective layer with a thickness of 5 μm.
[0106] <Example 5>
[0107] A negative electrode was obtained in the same manner as in Example 1, except that metal Zn particles (particle size (D50): 50 nm) and a binder (PVDF) were dispersed in an NMP solvent in a weight ratio of 7:3 so that the volume ratio of solid component:NMP solvent was 1:9, thereby forming a dispersion, and the resulting dispersion was coated on a lithium metal layer and dried to form a protective layer with a thickness of 5 μm.
[0108] <Example 6>
[0109] A negative electrode was obtained in the same manner as in Example 1, except that metal Ni particles (particle size (D50): 50 nm) and a binder (PVDF) were dispersed in an NMP solvent in a weight ratio of 7:3 so that the volume ratio of the solid component:NMP solvent was 1:9, thereby forming a dispersion, and the resulting dispersion was coated on a lithium metal layer and dried to form a protective layer with a thickness of 5 μm.
[0110] <Example 7>
[0111] A negative electrode was obtained in the same manner as in Example 1, except that SnO2 particles (particle size (D50): 3 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0112] <Example 8>
[0113] A negative electrode was obtained in the same manner as in Example 1, except that TiO2 particles (particle size (D50): 1 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 8:2 so that the volume ratio of solid component:NMP solvent was 3:7, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0114] <Example 9>
[0115] A negative electrode was obtained in the same manner as in Example 1, except that Li—Al (formed in a weight ratio of 7:3) alloy particles (particle size (D50): 1 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 8:2 so that the volume ratio of the solid component:NMP solvent was 3:7, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0116] <Example 10>
[0117] A negative electrode was obtained in the same manner as in Example 1, except that artificial graphite (particle size (D50): 9 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 8:2, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0118] <Example 11>
[0119] A negative electrode was obtained in the same manner as in Example 1, except that artificial graphite (particle size (D50): 9 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 9:1, thereby forming a protective layer slurry, and the resulting slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 40 μm.
[0120] <Experimental Example 1>
[0121] Use LiNi 0.8 Mn 0.1 Co 0.1 O2 as a positive electrode active material, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in a weight ratio of 96:2:2, and NMP as a solvent was added to the resulting mixture to prepare a positive electrode active material slurry.
[0122] For each side of the aluminum current collector, 5.01 mAh / cm 2 The positive electrode active material slurry is coated with a loading amount of , and then dried and rolled to obtain the positive electrode.
[0123] The electrolyte contains a solvent in which propylene carbonate (PC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:2:1 (PC:DEC:DMC). An electrolyte containing 1M LiFSI, 1M LiPF6 and 30 wt% of fluoroethylene carbonate (FEC) in the total amount of the electrolyte was prepared.
[0124] A polyethylene separator (thickness: 20 μm) was interposed between the negative electrode and the positive electrode of Comparative Examples 1 to 2 and Examples 1 to 10, and then an electrolyte was injected, and a CR2032 coin cell was manufactured according to a conventional method to obtain a lithium metal battery.
[0125] The fabricated lithium metal battery was charged under the following conditions and then disassembled, and the thickness and electrodeposition density of the lithium electrodeposition layer formed on the negative electrode were calculated and shown in Table 1 below.
[0126] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0127] The thickness of the electrodeposited layer was calculated by selecting any two points and obtaining the average thickness, and the electrodeposition density of the electrodeposited layer was quantified by calculating the precipitation mass and precipitation volume.
[0128]
Table 1
[0129] Thickness(μm) Density(g / cc) Comparative Example 1 100 0.1 Comparative Example 2 94 0.11 Example 1 24 0.43 Example 2 28 0.37 Example 3 38 0.27 Example 4 28 0.49 Example 5 45 0.22 Example 6 55 0.18 Example 7 30 0.35 Example 8 53 0.20 Example 9 36 0.29 Example 10 43 0.24 Embodiment 11 45 0.23
[0130] Referring to Table 1, it can be confirmed that, in the case of the present disclosure, the electrodeposition density is significantly increased.
[0131] In particular, it was confirmed that when a carbon-based material, lithium titanium oxide, or Sn-based particles were used, the electrodeposition density could be further increased, and the particle size was also affected.
[0132] Furthermore, it can be confirmed that the solid content also affects the porosity, which affects the improvement of the electrodeposition density. It can be confirmed that Example 1 having a reduced solid content and a high porosity has a higher electrodeposition density than Examples 10 and 11 which do not.
[0133] <Experimental Example 2>
[0134] The lithium metal battery manufactured in Experimental Example 1 was charged and discharged 200 times under the following conditions, and then the 200-time discharge capacity retention rate relative to the one-time discharge capacity was calculated, and the results are shown in Table 2 below.
[0135] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0136] Discharge: 0.5C, CC, 3.0V, cut-off
[0137]
Table 2
[0138]
[0139] Referring to Table 2, it can be confirmed that the electrodeposition density also affects the capacity retention rate, and in the case of the present disclosure, a remarkably excellent capacity retention rate is shown.
[0140] Based on the above disclosure, a person skilled in the art can make various applications and modifications without departing from the spirit and scope of the present disclosure.
[0141]
Industrial Applicability
[0142] As described above, the negative electrode according to one embodiment of the present disclosure forms a protective layer on the lithium metal layer, thereby having the effect of minimizing the reaction of the lithium metal with the atmosphere and reducing the increase in resistance during the assembly process of the secondary battery.
[0143] In addition, in a lithium metal battery comprising the negative electrode, the protective layer can absorb lithium during actual charge / discharge, thereby minimizing the thickness of the lithium electrodeposition layer formed on the protective layer and increasing the electrodeposition density, thereby minimizing the side reactions of the electrolyte and improving the life characteristics.
Claims
1. A lithium metal battery, wherein an electrode assembly is constructed in a battery case together with a lithium nonaqueous electrolyte, the electrode assembly comprising: a negative electrode for a lithium metal battery; a positive electrode having a structure in which a positive electrode mixture comprising an active material is coated on at least one surface of a positive electrode current collector; and a separator interposed between the negative electrode and the positive electrode, the negative electrode comprising: a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, and a protective layer formed on the lithium metal layer, wherein the protective layer contains a material capable of absorbing and releasing lithium in an amount of 70 wt % or more based on the total weight, The protective layer has a porosity of 1% to 70%, The amount of lithium that the positive electrode can provide is greater than the amount of lithium that the protective layer can absorb. The lithium metal battery can precipitate lithium on the protective layer during charge and discharge to form a lithium electrodeposition layer with a lithium density of 0.13 g / cc to 0.54 g / cc on the protective layer.
2. The lithium metal battery according to claim 1, wherein: The material capable of absorbing and releasing lithium includes a carbon-based material, a metal compound capable of alloying with lithium, a metal oxide, a lithium-metal alloy, or a mixture of two or more thereof.
3. The lithium metal battery according to claim 2, wherein the metal oxide is lithium metal oxide.
4. The lithium metal battery according to claim 1, wherein: The material capable of absorbing and releasing lithium includes a carbon-based material, SnO2 or a mixture thereof.
5. The lithium metal battery according to claim 1, wherein: The metal current collector substrate is one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper surface-treated with a different metal, stainless steel surface-treated with a different metal, and aluminum-cadmium alloy.
6. The lithium metal battery according to claim 1, wherein: The metallic current collector substrate is a metal comprising copper.
7. The lithium metal battery according to claim 1, wherein: The lithium metal layer has a thickness of 1 μm to 70 μm.
8. The lithium metal battery according to claim 1, wherein: The protective layer has a thickness in the range of 1 μm to 100 μm.
9. The lithium metal battery according to claim 1, wherein: The protective layer also includes an adhesive and a conductive material.
10. A method for manufacturing a lithium metal battery according to claim 1, comprising introducing an electrode assembly together with a lithium non-aqueous electrolyte into a battery case, sealing the battery case, and activating the resulting battery, The negative electrode in the electrode assembly is manufactured by a method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) mixing particles of a material capable of occluding and releasing lithium with a solvent to prepare a slurry; and (c) coating the slurry onto the lithium metal of step (a), The particles in step (b) have a particle size of 1 μm to 30 μm.
11. The method according to claim 10, wherein: The material capable of absorbing and releasing lithium includes a carbon-based material, SnO2 or a mixture thereof.
12. The method according to claim 10, wherein: In the step (b), the slurry is prepared such that the solid content of the slurry accounts for 30 volume % to 80 volume % based on the total volume of the slurry.
13. A method of manufacturing a lithium metal battery according to claim 1, comprising introducing an electrode assembly together with a lithium non-aqueous electrolyte into a battery case, sealing the battery case, and activating the resulting battery, The negative electrode in the electrode assembly is manufactured by a method comprising the following steps: (a) placing lithium metal on at least one surface of a metal current collector substrate; (b) dispersing particles of a material capable of occluding and releasing lithium in a solvent to prepare a dispersion; and (c) coating the dispersion onto the lithium metal of step (a), The particles in step (b) have a particle size of 1 nm to 1000 nm.
14. The method according to claim 13, wherein: The material capable of absorbing and releasing lithium includes a carbon-based material, SnO2 or a mixture thereof.
15. The method of claim 13, wherein: In the step (b), the dispersion is prepared such that the solid content of the dispersion accounts for 0.1 volume % to 30 volume % based on the total volume of the dispersion.
Citation Information
Patent Citations
A automatic ventilation system for condensation prevention
KR1020200144665A
Anode for lithium secondary battery and method for manufacturing same
CN111095616A
Anode comprising electrode protective layer and lithium secondary battery employing same
EP3474351A1
Negative electrode for lithium ion secondary battery
JP2012009209A
Negative electrode for lithium metal battery and lithium metal battery comprising the same
KR1020170124075A
